Dispersion of the G-type coal dust of the Vorgashorskoe field and its influence on the thermal destruction process - Vladimir A. Rodionov; Leonid V. Pikhkonen; Sergey Ya. Zhikharev (Perm Journal of Petroleum and Mining Engineering, 2017)
Results of a comprehensive study of coal dust obtained from the G-type coal of Vorgashorskoe field are presented. The main research methods used in the work are granulometric, thermogravimetric and differential thermal analysis. The granulometric sieving carried out confirmed the heterogeneity of the sample with size of 0-200 μm fraction for a technical analysis. It is established that fractions of less than 100 μm size account for more than 50 % of the total sample mass. The results obtained suggested that result can be different depending on the content of a fraction in the overall technical sample sent for an analysis. However, this is probably acceptable in a technical analysis of coal dust samples but not for determination of explosive and fire hazard indicators. In order to study the effect of the dispersion composition of dust on a pyrolysis process in the air (oxidizing) medium for each of the fractions of 0-200 μm and additionally for larger fractions studies were carried out using thermogravimetry and a differential thermal analysis. The thermogravimetric analysis confirmed the hypothesis about the ambiguous behavior of coal dust during its pyrolysis depending on the dispersion composition. Two fractions showed the same behaviont during the thermal pyrolysis. The fraction of 63-94 μm is the boundary one between 0-45 and 45-63 μm and remaining fractions of larger than 94 μm in size. That fact indicates that during determination of the explosive fire hazard properties it is necessary to investigate dust samples of dispersive composition from 0 to 100 μm, i.е. a narrower fraction than in the technical analysis of samples from 0 to 200 μm. Express analysis of the obtained data of differential thermal analysis showed a difference in thermal degradation between the fractions of interest at the initial stage (250-330 °C). The results obtained allowed to draw a conclusion about the expediency of the study of coal dust of dispersive composition from 0-100 μm. It also showed the necessity of using methods considered in the paper for a detailed study of physical and chemical parameters of coal dust and an assessment of its explosive and fire hazard properties.